Analisis Kinetika Perubahan Kualitas Fisik Terung Ungu (Solanum Melongena L.) Selama Penyimpanan - Hanis Adila Lestari; Amas Agung Pandu Prabowo; Christian Soolany (Jurnal Agritechno, 2020)
Eggplant is one of fruit much like by many people. Postharvest handling of eggplant could reduce losses due to short shelf life. One of the method to extend the shelf life of eggplant was stored at low temperature and soaked into solution of calcium cloride. The purpose of this research was to study kinetics eggplant quality during storage. Treatment to research was eggplant soaked in solution of calsium clorida (CaCl2) with concentration 0%, 1% and 2% then stored at 28°C and low temperature (9°C). Rate of quality is analyzed using kinetic equation. The kinetics of weight losses use zero-order, first-order was for hardness change and total dissolved solids. The research result showed that soaked into solution of calcium chloride (CaCl2) was capable of inhibiting the rate of change the quality of eggplant.